Mass and chemically speciated size distribution of Prague aerosol using an aerosol dryer--the influence of air mass origin - Schwarz, J; Štefancová, L; Maenhaut, W; Smolík, J; Ždímal, V (The Science of the total environment, 2012)
Ambient aerosol particles dried using a diffusional aerosol dryer were sampled using a 7-stage modified Berner low pressure impactor with a back-up filter during the heating and non-heating season campaigns in 2008. The samples were analyzed for water-soluble ions and water-soluble organic carbon. Because of the drying, the aerosol size distribution was not influenced by the daily variability of ambient relative humidity. The results summarize the observations from campaigns in both the heating (11 sampling days) and non-heating (10 sampling days) seasons. The aerosols sampled on individual days were classified based on the connected air mass back trajectories into three classes: sea-influenced aerosol (SIA), continental aerosol (CA) and mixed aerosol (MA) for samples of intermediate origin. The differences between CA and SIA were substantial both when looking at the normalized mass size distributions of the particulate matter (PM) and of the individual species and when taking into account the absolute concentrations in the fine and coarse size fractions. The main differences were found in the normalized mass size distributions of the PM and of the sea-salt related ions.
Keywords: Česká republika; látky znečišťující vzduch; Czech Republic; roční období; Environmental Monitoring; Air Pollutants; Aerosols; lidé; aerosoly; Particle Size; Particulate Matter; pevné částice; Seasons; monitorování životního prostředí; Heating; Humans; velikost částic; vytápění